A critical review on mechanical, durability, and microstructural properties of industrial by-product-based geopolymer composites - Elhag Ahmed Babeker; Raza Ali; Khan Qaiser uz Zaman; Abid Muhammad; Masood Bilal; Arshad Muhammad; Deifalla Ahmed Farouk (Reviews on Advanced Materials Science, 2023)
For the sustainability of the construction industry, geopolymers (GPMs) play an important role compared with Portland cement due to their improved mechanical properties, enhanced durability, and outstanding performance in alkali and acidic conditions. Most of the previous review investigations explored the general behavior of GPM developed with kaolin, silica fume (SF), rice husk ash, ground granulated blast furnace slag, fly ash, etc., but a comprehensive review study on the industrial by-products, including granite waste powder (GWP) and bauxite residue (BR), is required to investigate their suitability in the construction industry. The current investigation aims to present a detailed review of the fresh, mechanical, durability, and microstructural behavior of the GPM paste produced using BR and GWP from the literature. The effect of different ingredients and testing conditions are evaluated for the fresh, mechanical, durability, thermal, and microstructural performance of the GPM paste. The results indicate that the pure BR having a lower ratio of SiO2/Al2O3 reacts poorly; therefore, it should be blended with other aluminosilicates comprising a higher ratio of SiO2/Al2O3 for better geopolymerization. Pre-activation of BR including 3 h calcination at 800°C, 1 h thermal pretreatment of alkali with solid activators at 800°C, mechanical co-grinding, and pulverization presented improved strength and microstructural properties of GPM. When mixing GWP in large quantities, heat curing is preferred for 8 h at 60–80°C for better behavior of GPM. Incorporating the nanomaterials into GWP-based GPM showed a significant impact on initial compressive and tensile strengths. Further studies on the synergistic use of GWP with aluminosilicate products and BR with silica-rich pozzolanic ingredients for GPM are required. Improved physiochemical features of BR-GPM and GWP-GPM are the potential research areas that can be addressed by incorporating raw materials for enhancing the internal matrix, such as nanoparticles, bio-additives, micro-fibers, etc., that have been observed to be effective for the GPM pastes.